2017
DOI: 10.1007/s00262-017-2013-z
|View full text |Cite
|
Sign up to set email alerts
|

Dianthin-30 or gelonin versus monomethyl auristatin E, each configured with an anti-calcitonin receptor antibody, are differentially potent in vitro in high-grade glioma cell lines derived from glioblastoma

Abstract: We have reported that calcitonin receptor (CTR) is widely expressed in biopsies from the lethal brain tumour glioblastoma by malignant glioma and brain tumour-initiating cells (glioma stem cells) using anti-human CTR antibodies. A monoclonal antibody against an epitope within the extracellular domain of CTR was raised (mAb2C4) and chemically conjugated to either plant ribosome-inactivating proteins (RIPs) dianthin-30 or gelonin, or the drug monomethyl auristatin E (MMAE), and purified. In the high-grade glioma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 50 publications
0
28
0
Order By: Relevance
“…GPCRs are commonly targeted by small molecules but other approaches may be possible, for example, techniques to blunt GPCR expression, GPCR-directed antibodies, antibody-drug conjugates, and bio-conjugates. ( Junttila et al, 2015 ; Lelle et al, 2015 ; Gong et al, 2016 ; Gilabert-Oriol et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…GPCRs are commonly targeted by small molecules but other approaches may be possible, for example, techniques to blunt GPCR expression, GPCR-directed antibodies, antibody-drug conjugates, and bio-conjugates. ( Junttila et al, 2015 ; Lelle et al, 2015 ; Gong et al, 2016 ; Gilabert-Oriol et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…We therefore performed a preliminary screen by western blot for CALCR in our 4 HGG cell lines, which supported expressed protein of molecular weight and reactivity consistent with CTR in all 4 cell lines (see below). From this preliminary experiment we chose to further characterise these 4 cell lines, which appeared to have detectable CTR and were previously used in an anti-CTR immunotoxin study [25]. These cells were grown as adherent cultures in a monolayer on matrigel with EGF and FGFb growth factors that, in the absence of serum, showed a consistent morphology to previous publications (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In spite of this we could not detect a functional CTR response as assessed by cAMP accumulation (PB1, JK2, WK1) and i Ca 2+ assay (PB1 and WK1). However, we have previously shown that both JK2 and WK1 cell lines are susceptible to anti-CTR-immunotoxin (N-terminally directed) mediated cell killing [25]. In other systems, CTR has been reported to internalise extremely rapid in a ligand independent receptor manner [53, 55], suggesting that perhaps the CTR may not be present at the plasma membrane for sufficient time to generate detectable functional response in these GBM lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, Gilabert-Oriol et al determined the IC 50 value of recombinant His-tagged dianthin-30 chemically coupled to a monoclonal anti-calcitonin receptor antibody to 10–20 nM on high-grade glioma SB2b cells. A conjugate of the same antibody with the small molecule toxin monomethyl auristatin E revealed a similar cytotoxicity (IC 50 = 25.1 nM) [85] (Table 5).…”
Section: Dianthin Conjugates and Fusion Proteinsmentioning
confidence: 99%